An unusual and life-threatening presentation of a large GIST. (October 2022) - Saeidi, Nasrin; AlAli, Yousef; Boushehry, Reem; Al Safi, Sarah
Abstract: Introduction: Gastrointestinal stromal tumours (GIST's) are rare tumours of the alimentary tract. They are often discovered incidentally during imaging or intra-operatively. In rare instances, they present acutely with life threatening gastrointestinal (GI) bleeding requiring emergency surgical intervention. Case presentation: A 47-year-old gentleman, who is an ex-smoker with normal body mass index (BMI), presented with acute onset of epigastric pain, dizziness, and multiple episodes of melaena. The patient deteriorated rapidly and urgent endoscopy revealed active retrograde bleeding from beyond the duodenojejunal junction. Computed tomography angiography (CTA) suggested a highly vascular ileal exophytic mass resembling a GIST. Emergency exploratory laparotomy was conducted where hemostasis was achieved via segmental enterectomy of the mass that was unexpectedly jejunal in origin. During recovery, he encountered post-operative complications that were managed conservatively and eventually was discharged with a referral to the national cancer centre. Clinical discussion: The clinical presentation of GIST is based on its size and location. Definitive diagnosis of GIST relies on histopathological findings although the clinical presentation and imaging, in particular CTA, can aid in its diagnosis. Management of GIST differs depending on the clinical presentation, size, location and whether metastasis is present. Surgical resection is the standard of treatment; however, Imatinib could be used for non-resectable tumours as well as in cases of recurrence, metastasis or as an adjuvant chemotherapy. Conclusion: It is important to acknowledge that small GISTs are often asymptomatic while larger ones may present with non-specific symptoms which can be misleading. This could potentially delay the diagnosis and thus treatment of GIST which can be detrimental in acute cases as illustrated here. It is important to have GIST as one of the differentials when faced with a patient presenting with non-specific GI symptoms. Highlights: Although an acute presentation of GIST is rare, it must be recognised early to prevent further morbidity and mortality. The overlap between the symptoms of GIST and other GI disorders could lead to an uncertain diagnosis and thus unfavourable outcome. Imaging modalities along with immunohistochemical studies have eased the diagnosis of GIST The characteristics of the tumor largely influence the treatment pathway.